Killers of the flower moon : the Osage murders and the birth of the FBI - Grann, David (Yearling, an imprint of Random House Children's Books, a division of Penguin Random House LLC, 2022)
The Reign of Terror against the Osage people was one of history's most ruthless and shocking crimes. As the Wild West was dying, someone was killing members of the Osage nation who had gotten rich off the oil under their land. Investigators who tried to uncover the truth were disappearing, but still J. Edgar Hoover asked a former Texas Ranger to work with the Osage to unravel the mystery.